2016
DOI: 10.1093/schbul/sbw109
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Grey Matter Arteriolar Cerebral Blood Volume in Schizophrenia Measured With 3D Inflow-Based Vascular-Space-Occupancy MRI at 7T

Abstract: Metabolic dysfunction and microvascular abnormality may contribute to the pathogenesis of schizophrenia. Most previous studies of cerebral perfusion in schizophrenia measured total cerebral blood volume (CBV) and cerebral blood flow (CBF) in the brain, which reflect the ensemble signal from the arteriolar, capillary, and venular compartments of the microvasculature. As the arterioles are the most actively regulated blood vessels among these compartments, they may be the most sensitive component of the microvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 107 publications
0
31
0
1
Order By: Relevance
“…Due to advances in retinal and neuroimaging, it is now possible to study arteriolar, venular, and vasoregulatory mechanisms in vivo and there are a few studies implicating microvasculature disruption in patients with schizophrenia (Allen et al, 2016; Hua et al, 2016; Meier et al, 2013). Developmentally, a large longitudinal study showed that second trimester maternal angiogenesis levels were associated with narrower childhood retinal arteriolar caliber, but not with retinal venular caliber (Gishti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to advances in retinal and neuroimaging, it is now possible to study arteriolar, venular, and vasoregulatory mechanisms in vivo and there are a few studies implicating microvasculature disruption in patients with schizophrenia (Allen et al, 2016; Hua et al, 2016; Meier et al, 2013). Developmentally, a large longitudinal study showed that second trimester maternal angiogenesis levels were associated with narrower childhood retinal arteriolar caliber, but not with retinal venular caliber (Gishti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular abnormality may contribute to the pathophysiology of psychotic disorders, as evidenced by capillary ultra-structural damage, reduced blood flow, altered glucose metabolism, retinal microvascular abnormalities, uncoupling of cerebral blood flow/volume, and arteriolar cerebral blood volume reductions in SZ (Hua et al, 2016; Meier et al, 2013; Talati et al, 2015; Uranova et al, 2010; Uranova, 2013), and investigating angiogenic pathways may provide a novel biological framework for understanding these phenotypes (Lopes et al, 2015). Angiogenesis involves a balance between pro- and anti-angiogenic factors and can result in various pathological conditions (Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…BBB dysfunction was likewise observed in a boxer suffering from chronic traumatic encephalopathy [127]. In addition to the neurological problems, an aberrant microvasculature as well as abnormal CBF is observed in schizophrenia [128][129][130]. The cause of schizophrenia is not well-understood but may involve disturbed dopamine and NMDA receptor signaling.…”
Section: Neurodegenerative Diseases and The Brain Vasculature-an Emermentioning
confidence: 99%
“…Other regions, where hypoperfusion in SZ has been extensively documented, include middle and anterior cingulate, temporal and parietal regions (Ojeda et al, 2002; Schultz et al, 2002; Yucel et al, 2002) and thalamus (Clark et al, 2001). More recently, MRI based investigation of alterations in the volume of small arterial (pial) and arteriolar vessels in brains of individuals with SZ suggested that microvascular abnormalities maybe more widespread across the entire brain (Hua et al, 2016). Reduced CBF has been also associated with psychotic symptoms.…”
Section: Regional Brain Hemodynamic Changes Associated With Sz CLImentioning
confidence: 99%